Working hours of interns and internal medicine residents: a cross sectional study study - Sara Samadi; Atefeh Hosseinzadeh Bahabadi; Mahnaz Amini; Katayoun Samadi; Azita Ganji (Mashhad University of Medical Sciences, 2024)
Background: Duty hours for internships and residents have received globally criticism attention in recent years. Working hours highly affect trainee well-being, patient care, and education programs. There is no consensus about the benefit of reducing working hours. We aim to assess how reducing in work hours can influence interns on some aspects of training, well-being, and patient care.Method: This study was conducted in Internal Medicine Department of Imam Reza Hospital in Mashhad University of Medical Sciences, Iran. We reduced working hours from 20 hours to 10 hours in a shift for 6 weeks in our department for interns and a self-administered, validated questionnaire, which has previously been evaluated for the validity and reliability, was given to internal medicine residents and interns. At the end of the study, data were analyzed by SPSS.Results: A total of 11 residents and 23 interns completed the surveys. Limited working hours has significant beneficial effects according to participants' opinions in many domains with duty hour restrictions (P<0.05). These includes subdomains such as, increasing training and participating in their classes, well-being, improving the quality of file completion, more responsibility, better history taking, and less medical mistakes.Conclusion: As indicated, 83% of residents and 73% of interns reach a consensus on reducing the working-hours of the clinical rounds in many subdomains with duty hour reform. Their perceptions showed critical benefits in ability to deliver patient care, education and well-being after duty hour restriction.